CFD Simulation for Tray Dryer Optimization - Widodo, W. Sapto; Wong, C.Y; Kamarul, A.M; Hidayah, Nurul A. (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
The paper presents the design and analysis of tray dryer system. The design was done in Solidwork while the analysis and simulation performed using ANSYS FLUENT. ANSYS FLUENT is a Computational Fluid Dynamic (CFD) software in which flow fields and other physics are calculated in detail for various engineering applications. The analysis was done to analyze heat transfer and temperature distribution, ressure, air flow and turbulence. Before generating the product in 3D modeling, the basic data or information of tray dryer system is required such as dimension of dryer equipment, air and heat source supply range, sizing method and etc. Through his step, the dryer system development and function ability can be clearly understood by the end of analyzing process is accomplished.